2013
DOI: 10.1152/ajplung.00080.2013
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous osteopontin promotes ozone-induced neutrophil recruitment to the lungs and airway hyperresponsiveness to methacholine

Abstract: Inhalation of ozone (O₃), a common environmental pollutant, causes pulmonary injury, pulmonary inflammation, and airway hyperresponsiveness (AHR) in healthy individuals and exacerbates many of these same sequelae in individuals with preexisting lung disease. However, the mechanisms underlying these phenomena are poorly understood. Consequently, we sought to determine the contribution of osteopontin (OPN), a hormone and a pleiotropic cytokine, to the development of O₃-induced pulmonary injury, pulmonary inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 79 publications
(130 reference statements)
5
40
0
Order By: Relevance
“…5C). These data provide evidence of increased oxidative stress in lungs of obese mice even in the absence of a stressor such as O 3 .…”
Section: Bodymentioning
confidence: 61%
See 3 more Smart Citations
“…5C). These data provide evidence of increased oxidative stress in lungs of obese mice even in the absence of a stressor such as O 3 .…”
Section: Bodymentioning
confidence: 61%
“…2). Hyaluronan fragmentation and osteopontin are both required for O 3 -induced AHR in lean mice (3,14). O 3 increased both BAL hyaluronan and BAL osteopontin to a greater extent in Cpe fat than WT mice, and both BAL hyaluronan and BAL osteopontin were further augmented in Cpe fat / TNF-␣ Ϫ/Ϫ vs. Cpe fat mice (Fig.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Elevated OPN levels have been reported in the lungs of patients with asthma, COPD, or pulmonary fibrosis, or a combination of the above [7e11] and are linked to pathological features of these diseases, including eosinophil and neutrophil infiltration [12,13], goblet cell hyperplasia [14,15], airway hyper-responsiveness [13,14], and fibrosis [11,15,16]. Shan et al have recently demonstrated in mice that chronic exposure to CS induces Opn mRNA expression in lung dendritic cells, which in turn stimulates differentiation of Th17 cells and thus interleukin 17A (IL-17A)-driven inflammation, eventually leading to emphysema [17,18].…”
Section: Introductionmentioning
confidence: 99%